1999
DOI: 10.1021/jm980434t
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1-(2-Aminophenyl)isoquinolines and the Biological Activity of Their cis-Dichloro Platinum(II) Complexes

Abstract: The broad biological effects of isoquinolines prompted us to use them as chelating, nonleaving ligands in cis-platinum(II) antitumor complexes. The synthesis of several 1-(2-aminophenyl)isoquinoline derivatives with different levels of hydrogenation and varying substitution of the phenyl ring is reported. These compounds constitute a new class of ligands for the synthesis of oligocyclic platinum(II) complexes. In vitro cytotoxicity tests indicate that the most basic amine ligands afford the most effective comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…From group theory calculations, for C 2v coordination sphere geometry (PtN 2 Cl 2 ) two of each stretching vibrations of Pt-Cl and Pt-N should be of the A 1 and B 1 type, all IR active. Two bonds, detected in the range 329-342 cm À1 , can be assigned to Pt-Cl stretching vibrations as they are similar to those noted for some chloride complexes of Pt(II) with 4,7-H-5-methyl-7-oxo-1,2,4-triazole[1,5-a]pyrimidine (330 cm À1 ; this band is splits in two 335, 320 cm À1 ) [15], 1-(2-aminophenyl)isoquinoline derivatives (one band in range 328-335 cm À1 ) [32] and pyridine derivatives (average values 337 and 328 cm À1 ) [33]. The IR spectra contain also the bands at 280-287 cm À1 , those can be assigned to Pt-N stretching modes [34,35].…”
Section: Ir Spectrasupporting
confidence: 78%
“…From group theory calculations, for C 2v coordination sphere geometry (PtN 2 Cl 2 ) two of each stretching vibrations of Pt-Cl and Pt-N should be of the A 1 and B 1 type, all IR active. Two bonds, detected in the range 329-342 cm À1 , can be assigned to Pt-Cl stretching vibrations as they are similar to those noted for some chloride complexes of Pt(II) with 4,7-H-5-methyl-7-oxo-1,2,4-triazole[1,5-a]pyrimidine (330 cm À1 ; this band is splits in two 335, 320 cm À1 ) [15], 1-(2-aminophenyl)isoquinoline derivatives (one band in range 328-335 cm À1 ) [32] and pyridine derivatives (average values 337 and 328 cm À1 ) [33]. The IR spectra contain also the bands at 280-287 cm À1 , those can be assigned to Pt-N stretching modes [34,35].…”
Section: Ir Spectrasupporting
confidence: 78%
“…Some recent examples are cis-aminodichloropicolineplatinum(II) [19,20] and the transplatinum complexes with isoquinoline [21,22] and 1-(2-aminophenyl)isoquinoline ligands [23].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study reported that the copper (II) complex of fusaric acid possessed antimicrobial and strong cytotoxic activities against the human cancer lines KB, KBv200, and HepG2 (Tan et al, 2008). Some previous studies have demonstrated that coordination with metal ions can improve the anti-infective and antiproliferative activities of their respective ligands (Sanchez-Delgado et al, 1996;Navarro et al, 1997;Lowe et al, 1999;von Nussbaum et al, 1999). In particular, Bottari et al synthesized isoniazid-related copper (II), nickel (II), and cobalt (II) complexes with the aim of prolonging the drug effect and facilitating their diffusion through biomembranes (Bottari et al, 2000(Bottari et al, , 2001.…”
Section: Resultsmentioning
confidence: 99%